Association between maternal body mass index and congenital heart defects in infants: A meta‐analysis. (23rd January 2018) - Zhu, Yu; Chen, Yong; Feng, Yu; Yu, Di; Mo, Xuming
Abstract: We conducted this meta‐analysis to address the open question of a possible association between maternal body mass index (BMI) and congenital heart defects (CHDs) in infants. We conducted a comprehensive computerized search of PubMed, Web of Science, Medline, and Embase databased (January 1980 through August 2017). We assessed the association between maternal BMI and the risk for congenital heart defects in their offspring. Study‐specific relative risk estimates were polled according to random‐effect or fixed‐effect models. From 2567 citations, a total of 13 case‐control studies and 4 cohort studies were selected for a meta‐analysis, including more than 1 150 000 cases. The pooled odds radio (OR) of 1.065 (95% confidence interval [CI], 1.021‐1.100; P = .001; I 2 = 60.1%) indicated a positive effect of maternal overweight status (BMI 25.0–29.9 kg/m 2 ) on the risk for congenital heart defects in infants. Moreover, we observed a significant association between maternal obesity (BMI ≥ 30 kg/m 2 ) and congenital heart defects in their offspring (OR: 1.174; 95% CI, 1.146–1.203, P = 0.161; I 2 =25.5%). However, there was little significant evidence of an association between maternal underweight status (BMI < 18.5 kg/m 2 ) and offspring with congenital heart defects, and the pooled OR was 1.015 (95% CI, 0.980–1.052; P = 0.085; I 2 =34.0%). Our meta‐analysis provides robust evidence of the positive association between maternal BMI and the risk for fetal congenital heart defects.